A highly photoactive S, Cu‐codoped nano‐TiO2 photocatalyst: Synthesis and characterization for enhanced photocatalytic degradation of neutral red. Issue 2 (26th June 2013) - Yan, Chunyan; Yi, Wentao; Yuan, Hongmei; Wu, Xiaoxia; Li, Faqiang
<x xml:space="preserve">Abstract</x> Sulfur and copper codoped TiO2 (S, Cu‐TiO2) were prepared by sol‐gel process. And the samples were characterized by X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), UV‐vis diffuse reflectance spectroscopy (DRS), and N2 adsorption (BET method). The XRD results showed that the S, Cu‐codoped samples calcined below 550°C were pure anatase crystal structure which was in accordance with the FTIR spectra. "Red‐shift" in the UV‐vis spectrum of S, Cu‐codoped catalysts was observed, and SEM micrographs revealed that the codoped samples consisted of agglomerated nanoparticles with average particle size of 40–70 nm which was smaller than that of pure TiO2. The N2 adsorption measurements showed that the S, Cu‐codoped samples were mesoporous structures. The photocatalytic performance of the codoped samples was evaluated by monitoring the degradation of neutral red (NR) under UV and visible light illumination. The results showed that 0.2% S, Cu‐TiO2 calcined at 450°C had the highest photocatalytic activity among all samples. And the photocatalytic degradation rate of NR solution with a concentration of 20 mg L−1 could reach 98.4% under UV illumination in 120 min in the presence of 0.75 g L−1 catalyst and H2O2 with initial concentration of 0.2 mmol L−1. The kinetic study showed that this photocatalytic process coincided with the Langmuir‐Hinshelwood (L‐H) pseudo first order reaction model. The reusability study showed that 0.2% S, Cu‐TiO2 was highly stable up to third run. Therefore, the S, Cu‐codoped TiO2 is a promising candidate for degradation of NR containing wastewater. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 419–429, 2014